نظرية فيجوتسكي وتطبيقها في تعليم اللغة العربية - Widiya Yul (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: Learning Arabic through a second language acquisition theory has a positive contribution and effective in achieving the proficiency. Vygotsky's theory is one of the theories  second language acquisition, that have great importance in determining a person's ability to speak. But it can not be separated how lecture  to apply them in the learning.  Based on this study aims to evaluate and find a way of learning Ta'bir Syafahi using Vygotsky's theory by lecturer and effectiveness of the student with the application of the theory. This research also aim to find the quality of  Vygotsky's theory in the Arabic language acquisition the course ta'bir syafahi in achieving proficiency especially speaking skills. This study uses a qualitative approach which aims to determine the quantitative descriptive implementation Vygotsky is theory of learning in Ta'bir Syafahi in Ma’had Abdurrahman bin ‘Auf Malang.الملخص:إن تعليم اللغة العربية بإحدى نظريات اللغة الثانية لديه مساهمة إيجابية وفعالة في تحقيق الأهداف اللغة. من إحدى نظرية لإكتساب اللغة الثانية هي نظرية فيجوتسكي التي لها أهمية  كبيرة في تحديد الشخص على الكلام ولكن لا يمكن فصلها عن كيفية المدرّسة  التي تطبيقها في التعليم  والأهداف لهذا البحث التقويم و الكشف عن كيفية تعليم التعبير الشفهي باستخدام نظرية فيجوتسكي من جهة مدرّسات و الطالبات في معهد عبد الرّحمن بن عوف مالانج والكشف عن جودة نظرية فيجوتسكي في إكتساب اللغة العربية  في مادة التعبير الشفهي لتحقيق لمهارة الكلام. استخدم هذا البحث المنهج الكيفي الذي يهدف إلى معرفة الوصفي عن تطبيق نظرية فيجوتسكي في تعليم التعبير الشفهي في معهد عبد الرّحمن بن عوف بمالانج جاوا الشرقية.